(untitled) (Panacea Journal of Medical Sciences, 2022)
Background: Covid 19 infection came into existence in 2019 and hence the name. It started from a city in China named Wuhan. It continued to affect the whole world, so in 2020 it was declared as a pandemic outbreak and is prevalent worldwide till date. India is still suffering and struggling through its dreadful impact. The objective of this retrospective study is to analyze the laboratory parameters and to predict the severity/mortality related to the infection. Materials and Methods: A total of 312 hospitalized COVID-19 RTPCR positive patients from 1st April - 15 May 2021 were enrolled. Patients were categorized into deceased and non-deceased groups and their demographic as well as laboratory parameters were collected and compared. Results: Out of 312 patients, 100 succumbed to disease. Majorities were males between 55 to 60 years. The laboratory values of TLC (p<0 D-dimer(p=0.007717), p=0.000174), p=0.000085)> Conclusion: The attained results showed deranged laboratory parameters among COVID-19 positive patients. The mortality rate was found to be higher in elderly males as compared to females of same age group. There was significant correlation between the markedly abnormal laboratory values and severity/mortality of the COVID-19 infection, which could help in predicting the outcome of the disease in patients admitted to the hospitals.